Knowledge management in narrative / Ghazali Mohamed Fadzil. - Mohamed Fadzil, Ghazali (Universiti Teknologi MARA Cawangan Selangor, 2017)
The majority of the research on knowledge management (KM) in Malaysia has been testing-theory and deductive research in nature where elements and characteristics of good knowledge management are being identified. Also, limited researches that suggest effectiveness of different knowledge management system implementation. Such research does not really study the implications of KM and whether their implementations are successful or not. The limitation of such research in Malaysia necessitates exploring the use of new approaches in the pursuit of exploring and understanding further the subject matter. This article firstly, explains different types of research approaches. Secondly, proposes and argues on the suitability of a case study research with narrative inquiry as the main data gathering tool as an alternative. Thirdly, with a research example conducted on one organisation in Malaysia explains how data can be gathered and analysed.